Lower Back Pain, Blamed on Pregnancy, Ended Up with Worsening of Vision: A Case Report - Baltaziak, Katarzyna Anna; Małaczek, Maria; Tkaczyk, Jędrzej; Brożyna, Klaudia; Ciechański, Krystian; Nowakowska, Dominika; Rejdak, Robert (Journal of Education, Health and Sport, 2018)
A 51 year-old female was presented with worsening of vision in her right eye; left eye similar problem about one year earlier. Each time responded to methylprednisolone sodium succinate and her discharge diagnosis was the optic nerve neuropathy. The past medical history (PMHx) was remarkable for twenty years of hypertension, anemia of chronic disease and currently on hemodialysis due to her end stage renal disease (ESRD). The most notable part of PMHx was the sacral area pain since her pregnancy at age 28 which had never resolved until the radiational therapy for aneurysmal bone cyst (ABC) which was found in CT imaging. Since the lower back pain is a frequent complain in pregnancy and after deliveries, the complains were neglected until the tumor became unresectable. The radiation therapy produced the shrinkage of ABC, but caused renal injury leading to HTN and ESRD. At age approximately 48, the patient started experiencing worsening of her vision in her left eye, most likely in result of poorly controlled HTN while maintaining her normal vision in her right eye. As stated in the report, the patient was treated in our clinic for worsening of vision in her left eye followed by he vision worsening in her right eye within one year. During the most recent hospitalization a diagnosis of bilateral papilledema we established and left eye’s optic nerve head atrophy was confirmed using both OCT and MR imaging. We believe that ignoring common complaints can lead to uncommon complications causing the most severe consequences for our patients.